Analysis of systolic and diastolic blood pressure variability in frail, pre-frail, and non-frail elderly patients: The relationship between frailty syndrome and blood pressure variability in the elderly. Issue 8 (22nd February 2023) - Gu, Yan; Wan, Ying; Ren, Jue-Hui; Zhao, Yi; Wang, Yan; Shen, Jun-Hua
Abstract : Frailty can change the prognosis and treatment approach of chronic diseases. We, therefore, conducted this study to explore the relationship between frailty syndrome and blood pressure variability in the elderly. The clinical data of 150 elderly patients with debilitating syndrome admitted to the neurology department of our hospital from May 2021 to May 2022 were selected, and they were grouped according to Fried debilitation scale and divided into 50 cases each in the debilitation group, pre-debilitation group, and no-debilitation group. The general data, co-morbidities, medications, and biochemical indexes were collected. The 24-hour ambulatory blood pressure monitoring was performed in each group, and the mean systolic blood pressure, diastolic blood pressure, nocturnal systolic load value, and diastolic load value were analyzed to determine the relationship between blood pressure variability and senile frailty. Serum albumin (ALB) and high-density lipoprotein were significantly lower in the debilitated and pre-debilitated groups than in the non-debilitated group ( P < .05). Multivariate logistic regression analysis revealed that age (odds ratio [OR]: 3.910, 95% confidence intervals [CI]: 2.021–5.402) was a risk factor for frailty in the elderly, and serum ALB (OR: 0.656, 95% CI: 0.110–0.960) and HDL (OR: 0.581, 95% CI: 0.237–0.944) were protective factors for frailty in the elderly. Age, type of medication taken, co-morbidities, serum ALB, and HDL are influencing factors of debilitating syndrome. Serum ALB and HDL are protective factors against debilitating syndrome in the elderly. Age is an independent risk factor of debilitation in the elderly and increased fluctuation of blood pressure in the elderly can increase their risk of developing debilitating syndrome.